197k views
2 votes
6. Use the element method and proof by contradiction to prove that for any sets A,B and C, if B nCCA, then (C - A) n (B - A)=0.

User Npclaudiu
by
5.6k points

1 Answer

5 votes

Answer:

Suppose,

(C - A) ∩ (B - A) ≠ ∅

Let x is an element of (C - A) ∩ (B - A),

That is, x ∈ (C - A) ∩ (B - A),

⇒ x ∈ C - A and x ∈ B - A

⇒ x ∈ C, x ∉ A and x ∈ B, x ∉ A

⇒ x ∈ B ∩ C and x ∉ A

⇒ B ∩ C ⊄ A

But we have given,

B ∩ C ⊂ A

Therefore, our assumption is wrong,

And, there is no common elements in (C - A) and (B-A),

That is, (C - A) ∩ (B - A) = ∅

Hence proved...

User Sean Villani
by
5.1k points